2014
DOI: 10.1093/omcr/omu040
|View full text |Cite
|
Sign up to set email alerts
|

LMNA-related dilated cardiomyopathy

Abstract: A case of idiopathic dilated cardiomyopathy (DCM) that is likely to be associated with LMNA mutation Arg190Pro in a heterozygote is described. The features of DCM in the patient were conduction disorders, cardiac arrhythmias, progressive heart failure and minor musculoskeletal disturbances. We consider that the mutation Arg190Pro contributes to the formation of a weak nuclear lamina and diminishes muscle mechanical stability which is critical during cardiac contraction. The case report illustrates in detail th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In the heart, LMNA mutations cause up to 10% of dilated cardiomyopathies (DCM), [24] many coupled with progressive cardiac conduction system disease (CCD) or supraventricular arrhythmias. Prior studies indicate that conduction system disease commonly precedes DCM development by a few years to a decade or more [25] . In our study family, we found that the left and right atria of the proband were enlarged and the EF value was decreased slightly at age 53.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the heart, LMNA mutations cause up to 10% of dilated cardiomyopathies (DCM), [24] many coupled with progressive cardiac conduction system disease (CCD) or supraventricular arrhythmias. Prior studies indicate that conduction system disease commonly precedes DCM development by a few years to a decade or more [25] . In our study family, we found that the left and right atria of the proband were enlarged and the EF value was decreased slightly at age 53.…”
Section: Discussionsupporting
confidence: 57%
“…Prior studies indicate that conduction system disease commonly precedes DCM development by a few years to a decade or more. [ 25 ] In our study family, we found that the left and right atria of the proband were enlarged and the EF value was decreased slightly at age 53.…”
Section: Discussionmentioning
confidence: 62%
“…This would lead to molecular changes in the lamin A/C structure that can decrease the mechanical stability of the muscle, which is critical during muscle contraction. Several mutations were described at this position, most associated with DCM: p.Arg190Gln, p.Arg190Trp, p.Arg190fsX22 and p.Arg190Pro [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, common chronic heart failure and heart failure due to a rare genetic mutation (e.g. LMNA related dilated cardiomyopathy [ 23 ]) both share symptoms including fatigue, exercise intolerance, and limitation of activities of daily life [ 24 , 25 ]. Therefore, if physical activity measured by an actigraphy device has shown to be clinically relevant to disease progression for a common chronic heart failure, it is reasonable to generate such digital endpoints to rare cardiomyopathy.…”
Section: A Road Map To Dctmentioning
confidence: 99%